Revitalisasi Revitalizing Traditions through Community Services Activity: LASKAR Kencana (Preserving Traditions as Teenagers’ Creations) in Braja Kencana Village, East Lampung Regency - Prayudi, Vincentius Irvin; Amanda, Syakila; Miftah, Shaffa Riyadhul Jannah; Nizam, Fadhil Muhammad; Yani, Bela Aprida; Hamurwani, Auri; Ananta, Arya (Indonesian Journal of Community Services Cel, 2024)
The LASKAR Kencana (Preserve Traditions as Teenagers’ Creation/Lestarikan Adat sebagai Kreasi Anak Remaja) program in Braja Kencana Village, East Lampung Regency, is an initiative that mainly aims to revitalize local traditions through the youth creativity. This program, in the form of a community services activity, was designed to integrate traditional preservation with the development of creativity of the younger generation in Braja Kencana Village, so that village residents can play an active role in maintaining and preserving the cultural heritage of this village. This activity was carried out from June to August 2024 in Braja Kencana Village. The method used was a qualitative method with data obtained from this activity carried out by the community services team relating to social phenomena that occur in the Braja Kencana Village community. The method consisted of three stages: 1) analysis and identification regarding the community's interests and local potentials that can be developed, 2) implementation of program activities, and 3) evaluation and follow-up with village officials. Activities in the implementation stage included art training, traditional festivals, and development of digital media that displays village traditions. The results of this activity show an increase in children and teenagers' awareness of the importance of preserving customs and their success in creating innovations that are relevant to local culture. In conclusion, this program has not only managed to strengthen village’s cultural identity, but has also empowered the younger generation to become agents of change in their cultural context.